Microwave Assisted Hydrothermal Synthesis of TiO2 Nanorods for Photocatalytic Application - Anwar, Mohammad Shafique (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
In this work, TiO2 nanorods were grown using microwave assisted hydrothermal technique. The samples were characterized in detail by XRD, FE-SEM, Raman, and UV visible spectrometry techniques. Besides, photocatalytic characteristics were evaluated through measuring the degradation rate of methylene blue to establish a correlation between structure and photochemical properties. We were able to control morphology of the TiO2 nanorods by changing the reaction time during synthesis. The samples possessed a rutile phase and the crystallinity of the samples was significantly enhanced when the reaction time increased. The FE-SEM images show that nanostructures consist of several nanorods coming out of a single core and have very sharp edges. It was observed that the length and diameter of nanorod can be modified by changing the reaction time. The as prepared sample (for reaction time of 45 min) shows good photocatalytic activity. We established photocatalytic characteristics of TiO2 nanorods for technological application.